An Investigation of the Asymmetric Huisgen ‘Click’ Reaction - Stephenson, G. Richard; Buttress, James P.; Deschamps, Damien; Lancelot, Mélanie; Martin, James P.; Sheldon, Alexander I. G.; Alayrac, Carole; Gaumont, Annie-Claude; Page, Philip C. Bulman (Synlett, 2013)
The preparation of a series of new prochiral bis-alkynes is reported. A selection of chiral ligands is examined to gain additional information about the scope of the new asymmetric Huisgen ‘click’ reaction [the desymmetrisation of bis-alkynes using chiral ligands in conjunction with the widely applied copper-catalysed azide–alkyne cycloaddition (CuAAC) triazole synthesis]. The development of a new chiral assay for (±)-methyl 2-[(1-benzyl-1H-1,2,3-triazol-4-yl)methyl]-2-cyanopent-4-ynoate, and the production of this mono-triazole in up to 18% enantiomeric excess is described.
Keywords: chiral ligands; copper; CuAAC reaction; asymmetric synthesis